Pengaruh Ekstrak Daun Tabat Barito Terhadap Eosinofil Pada Kulit Mencit Alergi - Dindaswari, Eva Seviriria (STIKes Medistra Indonesia, 2023)
Allergy is a hypersensitivity reaction that occurs due to the induction of Immunoglobulin E antibodies against certain allergens associated with mast cells. Allergic reactions associated with inflammation are activated by released mediators. One of the inflammatory cells involved is eosinophils. Increased eosinophils can be suppressed by ursolic acid, total phenolics, and flavonoids. The aim of the study was to determine the effect of tabat barito leaf extract on the increase and decrease in eosinophil cells in mice skin induced by ovalbumin. This research was a pure experiment (True Experiment Research) with research samples in the form of 27 mice in 3 groups, namely the control, allergy, and allergy groups that were given the extract. This research was conducted at the Anatomical Pathology Laboratory, Kanujoso Djatiwibowo Hospital and the Hematology Laboratory, Medical Laboratory Technology Department, Poltekkes Kaltim. Data analysis was performed using the One Way Anova method to determine the effect of tabat barito leaf extract on allergic mice skin eosinophils. The results showed that the allergic group that was given the extract responded to a decrease in eosinophils on the 14th day when compared to the allergy group that was not given tabat barito leaf extract. The statistical test results obtained a p value of 0.000. It was concluded that there was an effect of giving tabat leaf extract on the reduction of eosinophil cells in the skin tissue of allergic mice given tabat barito leaf extract.